2019
DOI: 10.1111/cas.13974
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 signal modulators control the maintenance of hematopoietic progenitors in bone marrow and adult long‐term hematopoiesis

Abstract: Adult long‐term hematopoiesis depends on sustaining hematopoietic stem/progenitor cells ( HSPC ) in bone marrow ( BM ) niches, where their balance of quiescence, self‐renewal, and hematopoietic differentiation is tightly regulated. Although various BM stroma cells that produce niche factors have been identified, regulation of the intrinsic responsiveness of HSPC to the niche factors remains elusive. We previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…C3G is required for skeletal muscle and neuronal differentiation in vitro; [ 16 , 17 ]. Expression of constitutively active C3G in hematopoietic stem and progenitor cells enhanced their differentiation and depleted progenitor cell population in the spleen [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…C3G is required for skeletal muscle and neuronal differentiation in vitro; [ 16 , 17 ]. Expression of constitutively active C3G in hematopoietic stem and progenitor cells enhanced their differentiation and depleted progenitor cell population in the spleen [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin accessibility in BM LK cells showed loss of nearly half of the accessible peaks in Dpf2 Δ/Δ cells (27,271 of 60,147 peaks; Figure 6, D and E , and Supplemental Figure 6C ), mostly in intronic and intergenic regions ( Supplemental Figure 6D ), suggesting enhancer misregulation. We focused on the 7,400 peaks that lost assay for transposase-accessible chromatin using sequencing (ATAC-Seq) signal at least 2-fold in Dpf2 Δ/Δ LK cells, primarily located at introns and intergenic regions ( Supplemental Figure 6E ), and closely annotated to 3,420 genes enriched in critical pathways that regulate HSC proliferation and quiescence, including Rap1 ( 52 ), PI3K-AKT ( 53 ), and MAPK and RAS ( 54 ) signaling pathways ( Supplemental Figure 6F ). TF Motif analyses showed enrichment in NRF2/NFE2L2 binding motifs ( Figure 6F ), confirming loss of accessibility and transcription at antioxidant and antiinflammatory loci such as Nqo1 , Hmox1 , and Gclc ( Figure 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that TAGLN2 might regulate some upstream factors to activate the PI3K/AKT pathway in PTC. Nonetheless, studies demonstrate that Rap1 has an important regulatory effect on the PI3K/AKT pathway (Imai et al 2019). Rap1, a member of the Ras superfamily of small G proteins, has two states: an active GTP-bound state and an inactive GDP-bound state (Imai et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, studies demonstrate that Rap1 has an important regulatory effect on the PI3K/AKT pathway (Imai et al 2019). Rap1, a member of the Ras superfamily of small G proteins, has two states: an active GTP-bound state and an inactive GDP-bound state (Imai et al 2019). Rap1 activation is reported in various cancers and is recognized as a central regulator of multiple malignant processes, including proliferation, invasion, angiogenesis, and adhesion (Shah et al 2019).…”
Section: Discussionmentioning
confidence: 99%